Iron, phosphorus, and nitrogen supply ratios define the biogeography of nitrogen fixation. (21st October 2013) - Ward, Ben A.; Dutkiewicz, Stephanie; Moore, C. Mark; Follows, Michael J.
Abstract : We present a unified conceptual framework describing the competition between diazotrophs and non‐nitrogen‐fixing marine plankton and their interaction with three essential nutrient elements: nitrogen (N), phosphorus (P), and iron (Fe). The theory explains the global biogeography of diazotrophs and the observed large‐scale variations in surface ocean nutrient concentrations. The ratios in which N, P, and Fe are delivered to the surface ocean, relative to the demands of the phytoplankton community, define several biogeochemical provinces in terms of the limiting nutrients and the presence or absence of diazotrophs. Nutrient supply ratios provided by a global ecosystem model support the theoretical view that diazotroph biogeography is dominated by the Fe : N supply ratio, with the P : N supply ratio taking an important secondary role. The theory yields robust predictions for which strong empirical support is found in global observations of surface nutrient concentrations and diazotroph abundance.